(untitled) (Research, Society and Development, 2021)
This article compares Brazil, the United States, and Germany’s laws in the face of the COVID-19 pandemic, describing the scenario of these laws, comparing them to evaluate which country had the best performance, in their laws concerning the COVID-19, in the face of the international requirements. The primary laws of Brazil, the USA, and Germany were used, comparing WHO requirements and international requirements, analyzing: speed in the isolation decision; assembly of hospitals and equipment; economic measures for the population; organization of states and international negotiation. The comparison system established was based on scores (scores), with scores ranging from 1 to 5 (very poor to very good) depending on the existence of legislation for each country (Brazil, USA, and Germany), for each type of requirement, concerning the level of awareness of the norm’s applicator to the problems faced in the pandemic. Although some nations have acted quickly in imposing restrictions and recommending social isolation, they have been hampered by economic, social, and political factors.